2011
DOI: 10.3390/polym3031447
|View full text |Cite
|
Sign up to set email alerts
|

Photomechanical Response of Composite Structures Built from Azobenzene Liquid Crystal Polymer Networks

Abstract: Abstract:Optically directed shape adaptive responses have been sought after for many decades in photoresponsive polymeric materials. A number of recent examinations have elucidated elucidated the unique opportunities of photomechanical responses realized in azobenzene-functionalized liquid crystalline polymer networks (both elastomers and glasses). This work summarizes and contrasts the photomechanical response of glassy polydomain, monodomain, and twisted nematic azo-LCN materials to blue-green irradiation. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 33 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Most of the reported photomechanical response times for bulk solid materials (e.g., LC polymers) exposed to strong UV irradiation are on the order of seconds to minutes. For example, the films fabricated using a common H-azo and LC monomers displayed a slow response, ~30 s for a UV light intensity of 500–850 mW cm −2 with a UV irradiation dose (time × intensity) of 15–25 s W cm −2 41 , or several minutes for an intensity of 60–170 mW cm −2 (UV irradiation dose = 3.6–10.4 s W cm −2 ) 13 , 42 . Hosono et al reported on a fast, non-crosslinking polymer actuator that required UV irradiation for 10 s at an intensity of 300 W to trigger a photomechanical displacement of 2 mm with a UV irradiation dose of 3000 s W cm −2 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the reported photomechanical response times for bulk solid materials (e.g., LC polymers) exposed to strong UV irradiation are on the order of seconds to minutes. For example, the films fabricated using a common H-azo and LC monomers displayed a slow response, ~30 s for a UV light intensity of 500–850 mW cm −2 with a UV irradiation dose (time × intensity) of 15–25 s W cm −2 41 , or several minutes for an intensity of 60–170 mW cm −2 (UV irradiation dose = 3.6–10.4 s W cm −2 ) 13 , 42 . Hosono et al reported on a fast, non-crosslinking polymer actuator that required UV irradiation for 10 s at an intensity of 300 W to trigger a photomechanical displacement of 2 mm with a UV irradiation dose of 3000 s W cm −2 43 .…”
Section: Resultsmentioning
confidence: 99%
“…It is known that a laser beam carrying an optical vortex, when submitted to a static magnetic field, is able to induce in FFs whirlpool structures, very stable and reproducible (Figure k). Direct optical actuation of azobenzene‐functionalized liquid crystalline polymers was achieved in structures having the shape of a cantilever, in the millimeter range . The structure was effectively bent using a 100 mW/cm 2 radiation towards (away from) the light source using a polarization parallel (perpendicular) to the main cantilever axis.…”
Section: System Functionalitiesmentioning
confidence: 99%
“…Oscillating materials have attracted a great deal of attention over the last few years due to their potential application in a wide range of areas, for instance, micropumps and autonomous valves that simulate the heart's beating, photoactive polymers that mimic the cilia movement or the beat of the hummingbird's wings, artificial muscles for robotics, real-time optical information processors, molecular rotary motors and photoswitchable optical refl ectors [37][38][39][40][41][42][43][44][45][46][47]. Specifi cally, photochromic oscillators denote a specifi c class of photochromic switches that modify their optical properties periodically and extremely fast upon their exposure to light of the appropriate wavelength.…”
Section: Photochromic Oscillators Based On Fast Thermal Isomerizing Amentioning
confidence: 99%